Música no ensino fundamental: a lei 11.769/08 e a situação de escolas municipais de Santa Maria/RS - Ahmad, Laila Azize Souto (2011)
This dissertation was developed on Education Master s Course linked to the Program of Post-graduation on Education of the Federal Santa Maria University (Brazil), related to research interest number four: Education and Arts, also it s bound to Research Group Training, Action and Research on Musical Education. The general aim was to investigate the presence/absence of Music in municipal schools of Elementary School in Santa Maria, in order to know the possibilities for the 11.769/08 law s implementation, which guides the music as a required content to Basic Education schools. Specifically, it was sought (a) to verify how Teaching of Art discipline (or Arts Education) approaches and develops the musical contents in municipal schools of Santa Maria s Elementary School; (b) to map the material, physical and professional conditions existent in municipal schools, related to the Music; (c) to identify what are the institutional actions that schools are signaling to the process of 11.769/08 law s implementation. The methodological approach of this research was quantitative and qualitative, having as investigation method a survey of intersectional design. The participants of the study were pedagogic advisors of 46 municipal schools of Santa Maria s Elementary School and the data collect instruments were self-administered questionnaires. The analysis occurred through the initial data reduction in organizational frameworks. So, these were tabulated in the Excel Program, which resulted in tables and graphs. Then, it was developed the quantitative analysis based on SPSS Program. Finally, data were crossed and qualitatively analyzed, considering the literature review. In the first chapter, I discuss about educational policies, policy cycle approach, Basic Education and Basic Education in Santa Maria city. In the second one, I treat of educational policy related to the teaching of Arts and Music, having as a focus these laws: 5.692/71, LDB 9.394/96 and 11.769/08, respectively. After, I write about some researches on Music in Basic Education. As results, I d like to point that the Music is present in municipal schools investigated, mainly, in extracurricular activities. However, it s absent of sequential school practices, for many reasons, among them, the lack of material resources and physical space, also the absence of Music specialist teachers, which complicates the 11.769/08 law s implementation in the current situation of municipal schools of Santa Maria s Elementary School.